Vertical transition energies vs. absorption maxima: illustration with the UV absorption spectrum of ethylene - Lasorne, Benjamin; Jornet-Somoza, Joaquim; Meyer, Hans-Dieter; Lauvergnat, David; Robb, Michael A.; Gatti, Fabien (Spectrochimica acta. A, Molecular and biomolecular spectroscopy, 2014)
We revisit the validity of making a direct comparison between measured absorption maxima and computed vertical transition energies within 0.1eV to calibrate an excited-state level of theory. This is illustrated on the UV absorption spectrum of ethylene for which the usual experimental values of 7.66eV (V←N) and 7.11eV (R(3s)←N) cannot be compared directly to the results of electronic structure calculations for two very different reasons. After validation of our level of theory against experimental data, a new experimental reference of 7.28eV is suggested for benchmarking the Rydberg state, and the often-cited average transition energy (7.80eV) is confirmed as a safer estimate for the valence state.
Online 9 May 2013
Gesehen am 06.10.2020